The Human Tide: A Review Essay - Guinnane, Timothy W. (Journal of Economic Literature, 2021)
The Human Tide: How Population Shaped the Modern World, by Paul Morland, argues for the importance of demography in both historical events and our current situation. Intended for a general audience, the book traces demographic developments from the late eighteenth century, arguing that the timing and pace of demographic change helps to explain why some countries became powerful and others did not. The author continues the story into the twentieth century, discussing the changes in age structure and internal ethno-religious balances that are consequences of demographic patterns. Many readers will find the questions and themes in The Human Tide interesting. Unfortunately, the book misrepresents some research findings and is confused about important demographic concepts. The Human Tide deals with fundamental changes in human society over the past two centuries, but for a clear account of those changes, readers will have to go elsewhere. (JEL I12, J11, J13, J15, K37, N30)